1991
DOI: 10.1093/intimm/3.4.369
|View full text |Cite
|
Sign up to set email alerts
|

IgG response is impaired in H2-c-fos transgenic mice

Abstract: Transgenic mice carrying the proto-oncogene c-fos under the control of H-2Kb promoter (c-fos mice) were generated from (C57BL/6 x SJL)F2 mice. One line was backcrossed with C57BL/6 mice for 10 generations. These semi-congenic c-fos mice express exogenous c-fos RNA in their hematopoietic tissues. The following immunological states are apparent. (i) Titers of serum IgM, IgG, and IgA of naive c-fos were within the control range. (ii) These mice could not produce primary IgG antibody specific for immunized antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…7C). However, IgG1-AFCs were not detected at all in the bone marrow of the H2-c-fos mice, repeating the Ig-class switch abnormality of H2-c-fos mice (16,17). These results suggest that c-Fos/AP-1 positively regulates terminal differentiation of Ag-activated B cells.…”
Section: C-fos Augments Terminal Differentiation Of Ag-specific B Celmentioning
confidence: 83%
See 2 more Smart Citations
“…7C). However, IgG1-AFCs were not detected at all in the bone marrow of the H2-c-fos mice, repeating the Ig-class switch abnormality of H2-c-fos mice (16,17). These results suggest that c-Fos/AP-1 positively regulates terminal differentiation of Ag-activated B cells.…”
Section: C-fos Augments Terminal Differentiation Of Ag-specific B Celmentioning
confidence: 83%
“…We generated transgenic mice carrying the murine c-fos gene under the control of the murine MHC gene (H2-K b ) promoter (H2-c-fos) (15). Splenic T and B cells from the mice constitutively express a high level of the exogenous c-fos gene (16). When H2-c-fos mice are immunized with T-dependent Ags, the mice can make the reduced size of germinal centers and fail to generate memory B cells in the spleen (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments have demonstrated that overexpression of c-fos in transgenic and embryonic stem cell chimeric mice affects bone and cartilage cell lineages (7,22,27). With respect to hematopoietic cells, high levels of c-fos mRNA expression are found in macrophages, neutrophils, and T lymphocytes (6,16,20,21), and overexpression of c-fos in hematopoietic organs of transgenic mice results in an altered rate of T-cell maturation (23) and in impaired B-cell function (26). Furthermore, c-foslv-jun double-transgenic mice exhibit delayed development of early B cells and a low interleukin-7 (IL-7)-dependent proliferation capacity of bone marrow cells (5).…”
mentioning
confidence: 99%
“…Myc gene deregulation alone is not su cient to cause a fully transformed phenotype and requires the cooperative interactions of other gene(s) to induce a state of malignancy (Cleveland et al, 1986;Sinn et al, 1987;Cory and Adams, 1988;Harris et al, 1988;Kurie et al, 1990;Berns, 1991;Breuer et al, 1991;Takao et al, 1991). The ability of myc genes to participate in lymphomagenesis has been reported in transgenic mice that carry a deregulated c-myc gene (Adams et al, 1985;Leder et al, 1986;Suda et al, 1987;Schmidt et al, 1988;Alexander et al, 1989;Berns et al, 1989).…”
Section: Introductionmentioning
confidence: 99%